THE EFFECT OF INQURY BASED LEARNING ON THE PROCEDURAL KNOWLEDGE DIMENSION ABOUT ELECTRIC AND MAGNET CONCEPT (Jurnal Pendidikan Fisika Indonesia, 2017)
The purpose of this study to determine the effect of the use of inquiry-based learning to the increased dimensions of procedural knowledge in electrical magnetic material. The study used a quasi-experimental research methods with research design is non-equivalent control group design and a sampel are selected with the random sampling method. The experimental group was taught by the method of inquiry-based learning and the control group was taught by conventional methods. Collecting data using the instrument of multiple-choice test that developed through this research with category of validity is valid, reliability with category of reliable, index of discrimination with category of low, and level of difficulty with category of medium. The results of the data analysis by using the formula N-Gain and t-test showed that an increase in the dimensions of procedural knowledge siginificantly for experimental class and less significant for control class. Based on the results of this study suggested to the teacher to always use the method of inquiry learning that an increase in procedural knowledge dimension, especially for topics related to experimental physics.